Looking Into Mona Lisa’s Smiling Eyes: Allusion to an Illusion - Zavagno, Daniele; Actis-Grosso, Rossana; Daneyko, Olga (Frontiers in Human Neuroscience, 2022)
We present results from two experiments aimed at studying the direction of Mona Lisa’s gaze and its affective expression. In experiment 1 we studied the effect of retinal image size on the perception of her gaze by manipulating observation distances of a high-quality print of the painting. Participants (N=30) were asked to answer a simple question (is the person portrayed looking at you?) from 6 different distances ranging from 55 to 755 cm. One group of participants started evaluations from 55 cm; the other group did the opposite. Results show an effect of distance on the perception of Mona Lisa’s gaze as staring at the observer: from the furthest distances, the impression of a staring Mona Lisa is robust; from the nearest distances such impression becomes ambiguous. Experiment 2 presents data concerning the direction of Mona Lisa’s gaze and whether this appears to be smiling, derived from an experiment aimed at studying the impression of gaze (direction and emotional content) in portraits (paintings and fotographs). Only data concerning Mona Lisa are reported. Participants (N=41) were randomly assigned to one of two groups: on a CRT screen, one group saw the entire head, the other group saw only a section reproducing Mona Lisa’s eyes. Experimental sessions were 2: in session 1 participants had to decide whether the image (whole-head or eyes only) was looking at them; in session 2 participants had to decide whether the head (or the eyes) was smiling. RTs from the two groups of participants were not statistically significant. Results for session 1 confirm experiment’s 1 general findings. Results for session 2 clearly show that Mona Lisa is not only smiling with her face, but also with her eyes. Results are discussed in relation to the literature on Mona Lisa’s gaze and smile